1998
DOI: 10.1037/0021-9010.83.4.615
|View full text |Cite
|
Sign up to set email alerts
|

Participation in the performance appraisal process and employee reactions: A meta-analytic review of field investigations.

Abstract: The relationship between participation in the performance appraisal process and various employee reactions was explored through the meta-analysis of 27 studies containing 32 individual samples. The overall relationship (p) between participation and employee reactions, corrected for unreliability, was .61. Various conceptualizations and operationalizations of participation and employee reactions also were discussed and analyzed. Overall, appraisal participation was most strongly related to satisfaction, and val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
258
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(282 citation statements)
references
References 68 publications
(125 reference statements)
9
258
1
3
Order By: Relevance
“…According to Li and Butler (2004), the confidence of employees in the performance appraisal can be gained by getting them involved in the process of making choices relevant to their tasks. In this way, employees would be able to autonomously participate (self-reported performance) in the overall performance appraisal process and would feel satisfied with the performance appraisal procedure (Cawley, Keeping, & Levy, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…According to Li and Butler (2004), the confidence of employees in the performance appraisal can be gained by getting them involved in the process of making choices relevant to their tasks. In this way, employees would be able to autonomously participate (self-reported performance) in the overall performance appraisal process and would feel satisfied with the performance appraisal procedure (Cawley, Keeping, & Levy, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Also, empirical research shows that feedback will only lead to development and improvement of employees when they perceive the feedback as useful (Kinicki, Prussia, Wu, and McKee-Ryan, 2004). Hence, feedback reactions of employees can determine the success and effectiveness of their appraisal process (Cawley et al, 1998) and they are crucial for the acceptance and use of an appraisal system (Keeping and Levy, 2000). In our study, we focus on feedback utility as a dependent variable.…”
Section: Teacher Reactions To Teacher Performance Appraisalmentioning
confidence: 99%
“…In this regard, Levy and Williams (2004) suggest more research is needed to specify the effects of participation in the performance appraisal process. Also, Cawley, Keeping and Levy (1998) argue for more research regarding participation in performance appraisal focusing on different types of participation. In their review study, they demonstrated the positive effects of participation during the appraisal process itself (e.g.…”
Section: Teacher Participationmentioning
confidence: 99%
“…The fact that rating labels are misused is not a reason to avoid ratings. There is a large research literature in our field on how to improve reactions to performance evaluation (e.g., Bobko & Colella, 1994;Cawley, Keeping, & Levy, 1998;Dipboye & Pontbriand, 1981;Dorfman, Stephan, & Loveland, 1986;Giles & Mossholder, 1990;Ilgen, Peterson, Martin, & Boeschen, 1981;Pichler, 2012;Silverman & Wexley, 1984).…”
Section: Artificial Tradeoffs Are Driving Organizations To Abandon Ramentioning
confidence: 99%